Effects of Working Capital Management and Liquidity: Evidence from the Cement Industry of Bangladesh - Quayyum, Sayeda Tahmina (Journal of Business and Technology (Dhaka), 2012)
This paper is an attempt to investigate the effects of working capital management efficiency as well as maintaining liquidity on the profitability of corporations. For this purpose, corporations enlisted with the cement industry of Dhaka Stock Exchange have been selected and the analysis covers a time period from year 2005 to 2009. The purpose of this paper is to establish a relationship which is statistically significant, the other purpose is to help explain the necessity of firms optimizing their level of working capital management and maintaining enough liquidity as it affects the profitability. The result of this study clearly shows significant level of relationship between the profitability indices and various liquidity indices as well as working capital components. KEY WORDS: Working capital management; Liquidity; Cement Industry; Cash Conversion Cycle; Inventory Turnover; Receivables Turnover; Payable Turnover. DOI: http://dx.doi.org/10.3329/jbt.v6i1.9993 Journal of Technology (Dhaka) Vol. 6(1), January-June, 2011 37-47